Changes in the wage structure in EU countries - Rebekka Christopoulou; Juan F. Jimeno; Ana Lamo (European Central Bank (ECB), 2010)
We study changes in the wage structures in nine EU countries over 1995-2002 and the role of demand, supply and institutional developments in shaping these changes. Using comparable cross-country microeconomic data, we compute for each country and at each decile of the wage distribution, the part of the observed wage change that is due to changes in the composition of workers, employers, and jobs' characteristics, and the part due to changes in the returns to these characteristics. We find that composition effects derived from changes in age, gender or education of the labour force, largely exogenous to economic developments, had a minor contribution to the observed wage dynamics. In contrast, return and composition effects from characteristics likely driven by economic developments are found most relevant to explain the observed changes. We relate wages and their various components with macroeconomic and institutional trends and find that technology and globalisation are associated with wage increases; migration is associated with declines in wages; whereas the effect of labour market institutions has been mixed.
Keywords: J31; 330; Quantile Regressions; Wage Structure; Lohnstruktur; Lohnstruktur; Mikrodaten; Regressionsanalyse; EU-Staaten